YIELD AND PHYSIOLOGIC QUALITY OF POPCORN SEEDS, SUBMITTED TO MOLYBDENUM LEAF APPLICATION - ARAÚJO, Geraldo Antonio de Andrade; TEIXEIRA, André Ribeiro; MIRANDA, Glauco Vieira; GALVÃO, João Carlos Cardoso; ROCHA, Paulo Roberto Ribeiro (Scientia Agraria, 2010)
The goal of this work was to evaluate the effects of molybdenum increasing doses in popcorn crop, aiming to increasing the nutrient content in seeds, the influence of seed physiological quality and the crop yield. A field experiment was performed in a randomized block design, with four replications of seven doses of molybdenum (0, 50, 100, 200, 400, 800 and 1600 g ha-1). The doses of 0, 50, 100, 200 and 400 g ha-1 were applied 15 days after seedling emergence (DAE), the dose of 800 g ha-1 were applied in three portions as following: 400 g at 15 DAE, 200 g at 20 days and 200 g at 25 DAE; and the dose of 1600 g ha-1 in four equal portions of 400 g at 15, 20, 25 and 30 DAE. Yield components, nutrient content in leaves and seeds, and the seed physiological quality of popcorn were evaluated. The molybdenum content in leaves and seeds were influenced by the application of this micronutrient, reaching maximum values with the higher dose. The total number of seeds per plot and the yield were also influenced by molybdenum application, reaching maximum values of 21448 seeds and 4250 kg ha-1, with the doses of 680 g ha-1 and 1600 g ha-1, respectively. Molybdenum doses up to 1600 g ha-1 did not change the physiological quality of popcorn seeds.